BANKING SHORT- AND LONG-TERM STABILITY: A COMPARATIVE STUDY BETWEEN ISLAMIC AND CONVENTIONAL BANKS IN GCC COUNTRIES - Rihab Ben Slimen; Fethi Belhaj; Manel Hadriche (Copernican Journal of Finance & Accounting, 2022)
This research empirically assesses the contribution of Islamic finance to the financial stability of banks. The empirical analysis is based on the annual data related to 103 banks (51 Islamic banks and 52 conventional banks) operating in six countries of the Gulf Cooperation Council (GCC) region during the period 2006–2015. The LADR ratio was computed and used to measure banks stability in the short term, and the Z -score was used to assess long-term stability. The results show that, overall, Islamic banks are financially more stable in the short-term but less stable in the long term than conventional banks. The comparative analysis of the financial stability determinants in the two systems shows that these determinants contribute differently to the short- and long-term financial stability of Islamic and conventional banks. This is due to the dissimilarities in the two operating principles.